Handbook of Intelligence: Evolutionary Theory, Historical Perspective, and Current Concepts - Goldstein, Sam (Springer, 2016)
Numerous functions, cognitive skills, and behaviors are associated with intelligence, yet decades of research has yielded little consensus on its definition. Emerging from often conflicting studies is the provocative idea that intelligence evolved as an adaptation humans needed to keep up with – and survive in – challenging new environments. The Handbook of Intelligence addresses a broad range of issues relating to our cognitive and linguistic past. It is the first full-length volume to place intelligence in an evolutionary/cultural framework, tracing the development of the human mind, exploring differences between humans and other primates, and addressing human thinking and reasoning about its own intelligence and its uses. The works of pioneering thinkers – from Plato to Darwin, Binet to Piaget, Luria to Weachsler – are referenced to illustrate major events in the evolution of theories of intelligence, leading to the current era of multiple intelligences and special education programs. In addition, it examines evolutionary concepts in areas as diverse as creativity, culture, neurocognition, emotional intelligence, and assessment.